Digital Gaming for Improving the Functioning of People With Traumatic Brain Injury: Randomized Clinical Feasibility Study - Maritta Välimäki; Kaisa Mishina; Johanna K Kaakinen; Suvi K Holm; Jukka Vahlo; Markus Kirjonen; Virve Pekurinen; Olli Tenovuo; Jyrki Korkeila; Heikki Hämäläinen; Jaana Sarajuuri; Pekka Rantanen; et al. (My University, 2022)
Background
Traumatic brain injury (TBI) is a major health problem that often requires intensive and long-term rehabilitation.
Objective
The aim of this study was to determine whether rehabilitative digital gaming facilitates cognitive functioning and general well-being in people with TBI.
Methods
A total of 90 Finnish-speaking adults with TBI (18-65 years) were recruited from an outpatient neuroscience clinic. The participants were randomly allocated to one of the three groups: a rehabilitation gaming group (n=29, intervention), an entertainment gaming group (n=29, active control), or a passive control group (n=32). The gaming groups were instructed to engage in gaming for a minimum of 30 min per day for 8 weeks. Primary and secondary outcomes were measured at three time points: before the intervention, after the intervention, and 3 months following the intervention. The primary outcome was cognitive status measured by processing speed and visuomotor tasks (The Trail Making Test; Wechsler Adult Intelligence Scale-Fourth Edition, WAIS-IV, symbol search, coding, and cancellation tasks). Secondary outcomes were attention and executive functions (Simon task), working memory (WAIS-IV digit span and Paced Auditory Serial Addition Test, PASAT), depression (Patient Health Questionnaire-9), self-efficacy (General Self-efficacy Scale), and executive functions (Behavior Rating Inventory of Executive Function-Adult Version). Feasibility information was assessed (acceptability, measurement instruments filled, dropouts, adherence, usability, satisfaction, and possible future use). Cognitive measurements were conducted in face-to-face interviews by trained psychologists, and questionnaires were self-administered.
Results
The effects of rehabilitation gaming did not significantly differ from the effects of entertainment gaming or being in a passive control group. For primary outcomes and PASAT tests, the participants in all three groups showed overall improvement in test scores across the three measurement points. However, depression scores increased significantly between baseline and after 8 weeks and between baseline and after 3 months in the rehabilitative gaming group. No differences were found in patients’ self-efficacy between the three measuring points in any of the groups. Participants did use the games (rehabilitation group: 93%, 27/29; entertainment group 100%, 29/29). Games were seen as a usable intervention (rehabilitation group: 70%, 14/29; entertainment group: 83%, 20/29). The rehabilitation group was less satisfied with the gaming intervention (68%, 13/29 vs 83%, 20/29), but they were more willing to use the game after the intervention period (76%, 16/29 vs 63%, 15/29). Total time spent on gaming during the intervention period was low (15.22 hour rehabilitation gaming group, 19.22 hour entertainment gaming group).
Conclusions
We did not find differences between the groups in improvement in the outcome measures. The improvements in test performance by all three groups may reflect rehearsal effects. Entertainment gaming had elements that could be considered when rehabilitative games are designed for, implemented in, and assessed in larger clinical trials for persons with TBI.